National Assessment of Statin Therapy in Patients Hospitalized with Acute Myocardial Infarction: Insight from China PEACE-Retrospective AMI Study, 2001, 2006, 2011 - Zhang, Lihua (PLoS One, 2016)
BACKGROUND: Statin therapy is among the most effective treatments to improve short- and long-term mortality after acute myocardial infarction. The use of statin, and the intensity of their use, has not been described in acute myocardial infarction patients in China, a country with a rapidly growing burden of cardiovascular disease. METHODS AND RESULTS: Using a nationally representative sample of patients with acute myocardial infarction admitted to 162 Chinese hospitals in 2001, 2006 and 2011, we identified 14,958 patients eligible for statin therapy to determine rates of statin use and the intensity of statin therapy, defined as those statin regimens with expected low-density lipoprotein cholesterol lowering of at least 40%, to identify factors associated with the use of statin therapy. Statin use among hospitalized patients with acute myocardial infarction increased from 27.9% in 2001 to 72.5% in 2006, and 88.8% in 2011 (P<0.001 for trend). Regional variation in statin use correspondingly decreased over time. Among treated patients, those receiving intensive statin therapy increased from 1.0% in 2001 to 24.2% in 2006 to 57.2% in 2011(P<0.001 for trend). Patients without low-density lipoprotein cholesterol measured were less likely to be treated with statin or to receive intensive therapy. CONCLUSIONS: The use of statin therapy has dramatically increased over the past decade in Chinese patients with acute myocardial infarction. However, half of patients still did not receive intensive statin therapy in 2011.Given that guidelines strongly endorse intensive statin therapy for acute myocardial infarction patients, initiatives promoting the use of statin therapy, with attention to treatment intensity, would support further improvements in practice.